Effects of ranitidine and cisapride on acid reflux and oesophageal motility in patients with reflux oesophagitis: a 24 hour ambulatory combined pH and manometry study. Issue 8 (August 1993) - Inauen, W; Emde, C; Weber, B; Armstrong, D; Bettschen, H U; Huber, T; Scheurer, U; Blum, A L; Halter, F; Merki, H S
Abstract : The effect of ranitidine and cisapride on acid reflux and oesophageal motility was investigated in 18 patients with endoscopically verified erosive reflux oesophagitis. Each patient was treated with placebo, ranitidine (150 mg twice daily), and ranitidine (150 mg twice daily) plus cisapride (20 mg twice daily) in a double blind, double dummy, within subject, three way cross over design. Oesophageal acidity and motility were monitored under ambulatory conditions for 24 hours on the fourth day of treatment, after a wash out period of 10 days during which patients received only antacids for relief of symptoms. Acid reflux was monitored by a pH electrode located 5 cm above the lower oesophageal sphincter. Intraoesophageal pressure was simultaneously recorded from four transducers placed 20, 15, 10, and 5 cm above the lower oesophageal sphincter. Upright reflux was three times higher than supine reflux (median (range) 13.3 (3.7-35.0)% v 3.7 (0-37.6)% of the time with pH < 4.0, p < 0.01, n = 18). Compared with placebo, ranitidine decreased total reflux (from 10.0 (3.2-32.6)% to 6.4 (1.2-22.9)%, p < 0.01), upright reflux (p < 0.05), supine reflux (p < 0.001), and postprandial reflux (p < 0.01), but did not affect oesophageal motility. The combination of ranitidine with cisapride further diminished the acid reflux found with ranitidine--that is, cisapride led to an additional reduction of total reflux (from 6.4 (1.2-22.9)% to 3.7 (1.0-12.7)%, p < 0.01), supine reflux (p < 0.05), and postprandial reflux (p < 0.05). Cisapride also reduced both the number (p<0.01) and duration (p<0.05) of reflux episodes and significantly increased amplitude, duration, and propagation velocity of oesophageal contractions (p<0.05) but did not affect the number of contractions. The findings show that the 30% reduction of oesophageal acid exposure achieved by a conventional dose of ranitidine (150 mg twice daily) can be improved to more than 60% by combination with cisapride (20 mg twice daily). The cisapride induced increase in oesophageal contractile force and propagation velocity seems to enhance the clearance of gastro-oesophageal reflux. Combination of a histamine H2 receptor antagonist with a prokinetic agent may therefore provide an alternative treatment for reflux oesophagitis.